2021
DOI: 10.3390/v13112310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Serological Characterization of the SARS-CoV-2 Delta Variant in Bangladesh in 2021

Abstract: Novel SARS-CoV-2 variants are emerging at an alarming rate. The delta variant and other variants of concern (VoC) carry spike (S)-protein mutations, which have the potential to evade protective immunity, to trigger break-through infections after COVID-19 vaccination, and to propagate future waves of COVID-19 pandemic. To identify SARS CoV-2 variants in Bangladesh, patients who are RT-PCR-positive for COVID-19 infections in Dhaka were screened by a RT-PCR melting curve analysis for spike protein mutations. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The co-occurrence of the dip in S:P681H frequency with the emergence of S:Q677H and subsequent reversal are consistent with competition between these two substitutions. Both substitutions have proliferated at the global scale, suggesting that in some cases within-host and global dynamics may be aligned (Hodcroft et al 2021; Colson et al 2022; Ghosh et al 2021; Saxena et al 2022). Critically, S:Q677H peaked at a time (day 5 post-enrollment) when this participant was still viral culture positive (see figure 1 in (Ke, Martinez, Smith, Gibson, Achenbach, et al 2022)), indicating the potential for this de novo variant to be successfully transmitted.…”
Section: Resultsmentioning
confidence: 99%
“…The co-occurrence of the dip in S:P681H frequency with the emergence of S:Q677H and subsequent reversal are consistent with competition between these two substitutions. Both substitutions have proliferated at the global scale, suggesting that in some cases within-host and global dynamics may be aligned (Hodcroft et al 2021; Colson et al 2022; Ghosh et al 2021; Saxena et al 2022). Critically, S:Q677H peaked at a time (day 5 post-enrollment) when this participant was still viral culture positive (see figure 1 in (Ke, Martinez, Smith, Gibson, Achenbach, et al 2022)), indicating the potential for this de novo variant to be successfully transmitted.…”
Section: Resultsmentioning
confidence: 99%
“… 28 However, studies in India have suggested that this was the dominant strain in some cities prior to May 2021. 47 The B.1.617.2 variant, and its sublineages, is of particular concern for public health and the health care system due to its increased transmissibility compared to B.1.1.7 48 and increased resistance to neutralization by antibodies from plasma and serum. 49 Symptomatic and asymptomatic individuals with this variant are associated with more onward transmissions than similar individuals infected with the alpha variant 50 and, further, have a higher risk of hospitalization, need for intensive care unit admission, and mortality, 51 although other factors also contribute to this such as comorbidities, age, and vaccination status.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous targets, in addition to the P681R mutation, have been used to separate out the two lineages, including G142D and T478 K, which have also been used to screen patients with RT-qPCR. 47 The mutations L452R and E484Q within the receptor binding domain were specific to lineage B.1.617.1 (kappa) and B.1.617.3, while L452R and T478 K were specific to the lineage B.1.617.2, 59 although this mutation has also now been found in the B.1.617.1 (kappa), B.1.617.2 (delta), and B.1.427/B.1.429 (epsilon) variants. 60 In the present study, we used both targets (E484Q and P681R) initially to verify the presence of the B.1.617 lineage and later to differentiate between the kappa and delta variants when both variants were spreading, though a recent review reported that B.1.617.2 does not have the E484Q mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations